New insights into photochemical initial concentrations of VOCs and their source implications. (1st April 2023) - Li, Bowei; Yu, Shaocai; Shao, Min; Li, Xinhe; Ho, Steven Sai Hang; Hu, Xiaoyi; Wang, Hongli; Feng, Rui; Fang, Xuekun
Abstract: Volatile organic compounds (VOCs) photochemically react during the transportation from the source to the sampling site, which affects the understanding of their true characters from emissions. However, studies on the photochemical initial concentrations (PICs) of VOCs are still insufficient. Here, we propose an empirical coefficient that takes into account the combined effects of disturbances from new emissions and incomplete air mixing to calculate the PICs of non-methane hydrocarbons (NMHCs) (named "adjusted") and try to estimate the PICs of carbonyls. The relative consumption of NMHCs based on adjusted_PICs show better fits to O3 (r = 0.56 in winter and r = 0.65 in summer) in comparison with conventional_PICs (r = 0.33 in winter and r = 0.41 in summer). The adjusted_PICs of total NMHCs are higher than conventional_PICs in winter, while lower than conventional_PICs in summer. In contrast to measured concentrations, no obvious peaks of carbonyl PICs during noon times are found for acetone, propanal, and butanal in summer. Based on the adjusted PICs, higher contributions of solvent use and printing were apportioned compared with those based on measured concentrations and conventional_PICs, and no obvious contributions from secondary formation were identified. This study provides a new perspective for analyzing PICs and facilitates a clear understanding of VOCs sources. Highlights: An empirical factor is proposed to adjust the photochemical initial concentration (PIC) of VOCs. Relative consumption of NMHCs with adjusted_PICs correlates well with O3. PICs of carbonyls does not show obvious peaks during the day in summer. Higher contributions of solvent use and printing were apportioned based on the adjusted PICs.